Digital Populism: An Analysis of Donald Trump’s Rhetoric in X - Talukdar, Hoimawati; Borthakur, Medusmita; Herdono, Ismojo (Communicator: Journal of Communication, 2026)
This study examines the political discourse of Donald Trump on X during his return to office (2024–2025), with a focus on how his tweets construct polarized narratives across major geopolitical conflicts, including Russia–Ukraine, Israel–Palestine, Iran–Israel, the Houthis, India–Pakistan, and U.S. domestic politics. The primary objective is to analyze how Trump reproduces the "us versus others" ideological dichotomy in his digital communication. Methodologically, this study employs a qualitative approach using Critical Discourse Analysis (CDA) grounded in Van Dijk's (1997, 2006) ideological framework. A total of 20 tweets from Trump's official account were purposively selected and analyzed. The data were inductively coded into thematic categories, focusing on positive self-representation and negative other-representation, and were then subjected to an interpretative analysis of rhetorical and ideological patterns. The findings reveal that Trump systematically constructs a polarized discourse by portraying the United States, himself, and his political allies as strong and legitimate actors, while delegitimizing both domestic opponents (e.g., Democrats and media) and international actors (e.g., Iran, Hamas) as threats. A key finding is the strategic conflation of domestic and foreign adversaries, which reinforces exclusionary populist narratives. This study contributes to the literature by demonstrating the persistence of ideological patterns in digital populism and highlighting the role of social media in amplifying polarized communication. Practically, the findings provide insights into how political discourse in digital platforms shapes public perception and political polarization in contemporary democracies.